Anxiety and depression symptoms in different life stages - Grasso, Jimena Eliana (2025)
Symptoms of anxiety and depression represent a problem for health systems. Different sociodemographic variables affect the risk of suffering from them, among which is life stage. Given that the research literature is not clear about which age groups are at risk, the present research aimed to evaluate the symptoms of anxiety and depression in different age groups (18 to 24 years, 25 to 55 years and 56 to 65 years) of adults from CABA (35 %) and Greater Buenos Aires (65 %), considering interactions with gender and educational level. A sociodemographic questionnaire, the Beck Anxiety Inventory, and the Beck Depression Inventory were administered. The results show that the 18- to 24-year-old group reported higher levels of anxiety symptoms than the others. The 25- to 55-year-old group reported higher levels of depressive symptoms than the 56- to 65-year-old group. Regarding gender, those who reported female reported higher levels of anxiety and depression. Regarding the interaction between the variables, female people aged 25 to 55 reported higher levels of anxiety symptoms than males of the same age. Regarding the level of education, differences were found between groups, but the interaction with the age group variable was not significant. These results allow a greater understanding of the phenomenon and highlight the importance of addressing risk groups.